PENGARUH KUALITAS LAYANAN, PERSEPSI SUKU BUNGA, DAN PROMOSI TERHADAP PROSES PENGAMBILAN KEPUTUSAN NASABAH DALAM PENGAMBILAN KREDIT (Studi Pada Nasabah KUR Pada Bank Mandiri KCP Semarang Pamularsih - Taufiq Adi Prasetyo, 14.05.51.0095; Sutedjo, Bambang (Students' Journal of Economic and Management, 2018)
This study aims to determine and analyze the influence of service quality, interest rate perception and promotion of customer decision making process in credit taking at Bank Mandiri Pamularsih Branch Office. The sample in this study used population research techniques or census studies or saturated samples where all respondents were taken all as respondents ie as many as 97 respondents. Methods of data analysis using linear regression. From the research result can be taken some conclusion that service quality have positive and significant effect to customer decision in credit taking at Bank Mandiri KCP Semarang Pamularsih. The interest rate perception of the bank has a positive and significant impact on the decision of the customer in the credit taking at Bank Mandiri KCP Semarang Pamularsih. And promotions have a positive and significant impact on customer decisions in credit taking at Bank Mandiri KCP Semarang Pamularsih.. Keywords: service quality, interest rate perception, promotion and customer decision making process in credit collection